An intelligent lighting energy management system for commercial and residential buildings - Bannamas S. (2017)
© 2015 IEEE. This paper presents an intelligent lighting energy management system which is combined with six lighting control functions i.e. occupancy control, time scheduling, daylight control, task control, personal control and variable power shedding. There are two modes in the proposed lighting management system, which are the automatic and the personal control. Users can also control the system through the lighting management program and an internet web server. The lighting management system utilizing both natural and artificial light consists of the hardware, which is microcontroller and Raspberry Pi, and the software, which controls and manages the system. Furthermore, this paper proposes not only a method for choosing suitable functions in each area, but also a priority sequence method conforming to the two basic principles of efficiency in performance and effectiveness in light energy conservation. The experimental results showed that the proposed system could efficiently and effectively manage energy consumption. The system can be used to avoid energy waste, and saving energy consumption by a maximum of 68% in both switching and dimming control during typical days.